Victimization-precipitated residential mobility among women offenders - Yetter, Alyssa M. (Crime & delinquency, 2018)
Victims of crime are likely to move residence following their victimization. However, the reasons for and the outcomes of victimization-precipitated moves remain unclear. The current study uses life event calendar data on jailed women to test two potential mechanisms: relationship dissolution and perceptions of neighborhood safety. In addition, this study seeks to understand how the safety of women’s residential contexts is affected by their past victimizations and residential mobility. Results show that intimate partner victimization is associated with increased odds of moving, and this relationship is partially mediated by relationship dissolution. Furthermore, moving and nonpartner victimization interact in their effects on neighborhood safety, such that moves following higher levels of victimization lead women into more dangerous neighborhoods.